Metapher, Kontext und Kognition Metaphern zwischen Indexikalität und Ähnlichkeit - HESSE, Jacob (De Gruyter, 2022)
In this book, the author develops a theory of metaphors according to which metaphorical interpretations result from an interaction between certain linguistic properties of expressions and similarity-based processes of interpretation. Besides avoiding problems of other available theories of metaphor, his approach also provides valuable insights about other tropes such as irony or metonymy as well as about the relationship between semantics and pragmatics.